PERAN SERTIFIKASI GURU TERHADAP MOTIVASI DAN PROFESIONALITAS GURU DALAM MENINGKATKAN KUALITAS PENGAJARAN DI UPTD SD NEGERI 124394 JL. TONGKOL PEMATANGSIANTAR - Simanjuntak, Melvin M; Fuji Glory Simanjuntak; Eiren Florida Simamora; Yurianti Simanihuruk; Sandrina Gema Maria Simamora; Wawan Arinto Lingga; Dela Priska Manik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to examine in depth the impact of teacher certification on improving teacher competence and welfare at UPTD SD Negeri 124394 Jl. Tongkol, Pematangsiantar City. A quantitative approach was used in this study. Eight out of 18 certified teachers were interviewed and completed a comprehensive questionnaire to gain a better understanding of their experiences and perceptions regarding certification. This quantitative approach also used observations, interviews and questionnaires to obtain data from certified teachers. The aim is to measure the effect of certification on the variables under study directly. The results showed that teacher certification at UPTD SD Negeri 124394 Jl. Tongkol, Pematangsiantar City significantly improved teachers' personality competence, social competence, pedagogical competence and professionalism competence. Certified teachers tend to have more in-depth knowledge of the curriculum, innovative learning strategies and methods, and the ability to manage the classroom. Certification also improves teachers' welfare financially through professional allowances and personal income. This study is interesting because it found no significant challenges faced by teachers after obtaining certification. This suggests that the certification program is effective and can meet teachers' professional development needs.